Construction of remote control for web based street light pole - Mo Kim, Yong (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is not easy to ascertain a maximum electricity production in case of solar energy generation and there is problem not to recognize failures for a long time even iffailures occurred in facility. Measures need to be taken not only to check irregularities and replacement time but to maximize overall efficiency of solar energy generation system.Methods/Statistical analysis: It is necessary to build a control system based on web to analysis of various statistics information and real time index visibility. It is also necessary to verify SMS notification in the number of lightning in case of the falling of a thunderbolt, date and time of the occurrence, and correct operation of circuit breaker in the connection board.Findings: It is needed to be introduced the system which not only considers excessive communication cost as well as failure treatment of communication device and replacement cost but also makes full use of a dispersed generating system. Control system which is able to do scientific action of making up for fault and proper monitoring as well as maintenance in a solar power plant is constructed in this study.Improvements/Applications: Smart control system that electricity generation is stopped or reactivated in case of emergency through making an autonomous judgment of difficulties or faulted conditions will be extended. Technology of new renewable energy such as wind power and geothermal power will be applied through enhanced design technology of communication interface.Â Â